2009
DOI: 10.1590/s1678-77572009000600014
|View full text |Cite
|
Sign up to set email alerts
|

Micromorphology and microhardness of enamel after treatment with home-use bleaching agents containing 10% carbamide peroxide and 7.5% hydrogen peroxide

Abstract: Objective:The purpose of this study was to assess the effect of home-use bleaching agents containing 10% carbamide peroxide and 7.5% hydrogen peroxide on enamel microhardness and surface micromorphology.Material and Methods:Enamel slabs (n=10) received the bleaching agents for 1 h/day and remained in artificial saliva solution for 23 h/day, during a total period of 21 days. Control group was composed of enamel slabs that were not subjected to treatment with the agents and were maintained in artificial saliva s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
4
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 12 publications
7
53
4
9
Order By: Relevance
“…The highest micro-roughness in conventional method was due to the high pH level of Kimia gel used in the process. The results of this study were in accordance with the studies of Pinto et al, 11 Dominguez et al, 12 De Vasconcelos et al, 13 and Sasaki et al, 14 which reported that in-office bleaching increases surface roughness of enamel. The results of the present study were in contrast with the results of McGuckin et al, 15 Mondelli et al 16 and Borges et al 17 which indicated that in conventional bleaching procedure, the enamel micro-roughness could not increase.…”
Section: Discussionsupporting
confidence: 92%
“…The highest micro-roughness in conventional method was due to the high pH level of Kimia gel used in the process. The results of this study were in accordance with the studies of Pinto et al, 11 Dominguez et al, 12 De Vasconcelos et al, 13 and Sasaki et al, 14 which reported that in-office bleaching increases surface roughness of enamel. The results of the present study were in contrast with the results of McGuckin et al, 15 Mondelli et al 16 and Borges et al 17 which indicated that in conventional bleaching procedure, the enamel micro-roughness could not increase.…”
Section: Discussionsupporting
confidence: 92%
“…From the toxological point of view pomegranate peel extract is safe & non-toxic. [10][11][12] Oligomeric proanthocyanidins are a class of polyphenolic bioflavonoids found in fruits and vegetables (grape seed extract, cranberries, pine bark extract, hazel nut tree leaves, lemon tree bark etc). They have free radical scavenging and antioxidant activity with added antibacterial, antiviral, anti-inflammatory, anti-allergic, anticarcinogenic, and vasodilatory actions.…”
Section: Discussionmentioning
confidence: 99%
“…Sasaki et al 45 observed that home‐bleaching agents may lead to microalterations in the surface micromorphology of enamel with no alterations in microhardness. Ito and Momoi (2011) demonstrated, on SEM images, that the increase in enamel surface roughness, and erosion depth due to 30% hydrogen peroxide were smaller when the bleaching product was in addition with NaHCO2.…”
Section: Discussionmentioning
confidence: 99%